Ordbok eller encyklopedi - en fråga om hänsyn till användaren? - Lundbladh, Carl-Erik (Nordiske Studier i Leksikografi, 1997)
This article investigates the possibility of distinguishing between, on the one hand, dictionaries describing linguistic phenomena and, on the other hand, dictionaries prirnarily providing information about extra-linguistic matters. The description of meaning is considered to be a normal feature of what we call dictionaries, but there is sometirnes uncertainty or disagreement about what meaning is and how it can be delirnited from information about the things denoted by the words. It can be difficult or irnpossible to find theoretically tenable criteria for the difference between meaning and encyclopaedic information. This is not, however, the same as saying that there is no difference.